A study on the tilt effect of pressure balance up to 500 MPa. (December 2021) - Ginanjar, Gigin; Choi, In-Mook
Abstract: It is known that the tilt effect of pressure balances appears to be a cosine effect. However, the piston tilt against the cylinder would result in the effective area change according to the pressure in addition. The relative tilt effect of the piston against the cylinder has not been studied much. In this paper, the piston tilt effect is analyzed up to 500 MPa by 3D (three-dimensional) Finite Element Analysis (FEA) since it is not possible to analyze the effective area change due to the piston tilt using the 2D FEA which is axis-symmetric. According to the FEA results, the piston tilt effect can be negligible up to 100 MPa, but the effect increases significantly over 100 MPa. The effective area changes between theoretical, simulation and experimental results are compared at the maximum piston tilt condition.